Vascular Adhesion Protein 1 Mediates Gut Microbial Flagellin-Induced Inflammation, Leukocyte Infiltration, and Hepatic Steatosis - Toivonen Raine; Vanhatalo Sanja; Hollmén Maija; Munukka Eveliina; Keskitalo Anniina; Pietilä Sami; Elo Laura; Huovinen Pentti; Jalkanen Sirja; Pekkala Satu (MDPI, 2025)
Toll-like receptor 5 ligand, flagellin, and vascular adhesion protein 1 (VAP-1) are involved in non-alcoholic fatty liver disease. This study aimed to determine whether VAP-1 mediates flagellin-induced hepatic fat accumulation. The effects of flagellin on adipocyte VAP-1 expression were first studied in vitro. Then, flagellin (100 ng/mouse) or saline was intraperitoneally injected into C57BL/6J (WT) and C57BL/6-Aoc3-/- (VAP-1 KO) mice on a high-fat diet twice a week every 2 weeks for 10 weeks. After that, the effects on inflammation, insulin signaling, and metabolism were studied in liver and adipose tissues. Hepatic fat was quantified histologically and biochemically. Because flagellin challenge increased VAP-1 expression in human adipocytes, we used VAP-1 KO mice to determine whether VAP-1 regulates the inflammatory and metabolic effects of flagellin in vivo. In mice, VAP-1 mediated flagellin-induced inflammation, leukocyte infiltration, and lipolysis in visceral adipose tissue. Consequently, an increased release of glycerol led to hepatic steatosis in WT, but not in KO mice. Flagellin-induced hepatic fibrosis was not mediated by VAP-1. VAP-1 KO mice harbored more inflammation-related microbes than WT mice, while flagellin did not affect the gut microbiota. Our results suggest that by acting on visceral adipose tissue, flagellin increased leukocyte infiltration that induced lipolysis. Further, the released glycerol participated in hepatic fat accumulation. In conclusion, the results describe that gut microbial flagellin through VAP-1 induced hepatic steatosis.